2020
DOI: 10.2147/cia.s236998
|View full text |Cite
|
Sign up to set email alerts
|

<p>Driver Self-Regulation Practices in Older Drivers with and Without Mild Cognitive Impairment</p>

Abstract: Objective: To assess the impact of cognitive, socio-demographic and driving-related characteristics on self-regulation practices in older drivers with mild cognitive impairment (MCI) (determined by the Telephone Cognitive Screen (T-CogS) score), compared with drivers with no cognitive impairment. Design, Setting, Participants: A cross-sectional study collected information from 362 drivers with MCI and 611 drivers with no cognitive impairment, who were aged 65+ years, and were living in Western Australia betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
(48 reference statements)
3
9
0
1
Order By: Relevance
“…In our sample, younger people, males, and those with longer driving experience were more likely to be current drivers, in the light of demographic and driving-related characteristics. A similar pattern emerged in several previous studies [49][50][51]. As expected, current drivers performed better in neuropsychological testing than retired ones, which is in agreement with the findings of Vaughan et al [52].…”
Section: Discussionsupporting
confidence: 92%
“…In our sample, younger people, males, and those with longer driving experience were more likely to be current drivers, in the light of demographic and driving-related characteristics. A similar pattern emerged in several previous studies [49][50][51]. As expected, current drivers performed better in neuropsychological testing than retired ones, which is in agreement with the findings of Vaughan et al [52].…”
Section: Discussionsupporting
confidence: 92%
“…Drivers with minor impairment might minimise collision risk through selfregulation of their driving practices. 5 Hence, realworld epidemiological research is required to better quantify the collision risk associated with medication use. A comprehensive review of epidemiological research on this topic identified cohort designs comparing collisions in people taking medication versus those not taking medication, standard casecontrol designs comparing medication use in drivers involved in a collision with drivers who were not involved in a collision, and caseonly designs such as casecrossover studies and responsibility analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Participants were recruited from the initial 1001 drivers who completed the first phase of the study (telephone interview). 26 Those who met eligibility requirements, expressed an interest and agreed to participate in the naturalistic driving phase of the study, were recruited between October 2019 and March 2020.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…This cross-sectional naturalistic driving study examining speeding events in older drivers is part of a larger prospective cohort study examining the association between cognitive ability and driving. [26][27][28] Speeding events, which were measured using an in-vehicle monitoring device over a two-week period, were examined in 35 older drivers with suspected MCI, defined by the Montreal Cognitive Assessment (MoCA), and 36 older drivers with no cognitive impairment.…”
Section: Methodsmentioning
confidence: 99%